Long-Run and Short-Run Relationships Between Covid-19 and the Loss of Employment in Malaysia: Evidence Using GARCH-M, EGARCH-M and PGARCH-M Models = Relações de Longo e Curto Prazo Entre Covid-19 e Perda de Empregos na Malásia: Evidência Usando Modelos GARCH-M, EGARCH-M e PGARCH-M - Muzafar Shah, Habibullah; Evan, Lau; Badariah, Haji Din; Muhammad Daaniyall, Abd Rahman; Musalman Ahmad, Iskandar Shah (Portuguese Association for Regional Development (APDR)., 2022)
The purpose of the present paper is to investigate the long-run and short-run relationships between the loss of employment and the Covid-19 pandemic in Malaysia’s labour market. The Covid-19 measures in-clude the number of Covid-19 new cases, the number of Covid-19 new deaths, the number of total Covid-19 cases and the Covid-19 fear index. Using cointegration analysis, we found that the loss of employment exhibit long-run relationships with the four Covid-19 measures. Our short-run analysis using the PGARCH-M model able to captures the volatility and clustering of the variability in the loss of employment. The PGARCH-M model shows evidence of the leverage effects or asymmetric effects which suggest that the positive shocks (good news) increase volatility in the loss of employment, more than the negative shocks (bad news) in a crisis situation.